Optimizing Anaerobic Co-Digestion Formula of Agro-Industrial Wastes in Semi-Continuous Regime - Ana I. Parralejo; Jerónimo González; Luis Royano; Juan F. González (Energies)
The actual environmental and energy crises are two of the main problems existing in the world. Among the different technologies that can be implemented is anaerobic digestion, which employs waste and renewable biomass materials. To reach the optimum ratio of different raw materials or substrates in the feed of digesters, laboratory tests are necessary. This work aims to study the increase in the Organic Load Rate (OLR) (1 g VS L−1d−1, 2 g VS L−1d−1, 3 g VS L−1d−1 and 4 g VS L−1d−1, VS: Volatile Solid) and the raw materials number (sorghum (S), pig manure (P), triticale (T), corn stover (C) and microalgae biomass (M)) in the feedstock of the anaerobic digestion process. Mean values of methane yields for the evaluated set were lower in SMP and SMPTC assays (149.80 LCH4 kg VS−1 and 157.15 LCH4 kg VS−1, respectively) than SP, SM and SMPT assays (195.09 LCH4 kg VS−1, 197.69 LCH4 kg VS−1 and 195.76 LCH4 kg VS−1, respectively). Along the experiments, several parameters were evaluated, along with their interactions with OLR and number of raw materials. Two kinetic models were employed to fit the COD (Chemical Oxygen Demand) removal results.